2019
DOI: 10.3897/mycokeys.47.31130
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and morphological studies in Xylodon (Hymenochaetales, Basidiomycota) with the addition of four new species

Abstract: Xylodon (Hymenochaetales, Basidiomycota) is the largest segregate genus of Hyphodontia s.l. Based on molecular and morphological data, 77 species are accepted in Xylodon to date. Phylogenetic analyses of ITS and 28S sequences, including 38 new ITS and 20 28S sequences of Xylodon species, revealed four species new to science. The new taxa X.exilis, X.filicinus, X.follis and X.pseudolanatus from Taiwan, Nepal, Réunion, Belize, and USA are described and illustrated. In addition, species concepts for Odontiavesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Hyphodontia s.l. is an extensively studied group of Hymenochaetales (Dai 2012;Viner et al 2018;Riebesehl et al 2019), but the Chinese species diversity is still not well known, especially in subtropical and tropical areas. The four new Lyomyces species here described are from the subtropics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyphodontia s.l. is an extensively studied group of Hymenochaetales (Dai 2012;Viner et al 2018;Riebesehl et al 2019), but the Chinese species diversity is still not well known, especially in subtropical and tropical areas. The four new Lyomyces species here described are from the subtropics.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies on Lyomyces and related genera have been carried out recently Yurchenko et al 2017;Viner et al 2018;Riebesehl et al 2019). Riebesehl and Langer (2017) indicated that Hyphodontia s.l.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research showed that Xylodon was strongly supported to be a monogenetic genus in Hyphodontia s.l. by the mycologists [14,23,30]. According to our result based on present sequence data (Figure 2), X. gossypinus, X. macrosporus, and X. sinensis are nested into Xylodon with strong supports.…”
Section: Discussionmentioning
confidence: 51%
“…The identity of all samples named under X. australis was confirmed by molecular data (see Supplementary Figs. S1-S3 on line) and their phylogenetic position among other Xylodon species was according to Riebesehl et al 17 . The number of constant, variable, uninformative and informative characters under maximum parsimony analyses are indicated in the legend of the Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%